Pengaruh Harga dan Kualitas Produk terhadap Minat Beli Konsumen PT. Frisian Flag Indonesia di Cabang Pekanbaru - Ferisca Nurwidyanti; Jeli Nata Liyas (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study aims to analyze the effect of price and product quality on consumer purchasing interest at PT. Frisian Flag Indonesia in Pekanbaru Branch. The sample used in this study consisted of 50 consumers. Data analysis was carried out using several techniques, including validity tests, reliability tests, classical assumption tests, multiple linear regression, hypothesis tests, and coefficient of determination tests. Based on the results of the study, the t test shows that price has a significant influence on consumer purchasing interest, with a t-count of 2.908 which is greater than t-table 2.010 and a significance value of 0.005 which is smaller than 0.05. Similarly, product quality also has a significant effect on purchasing interest, with a t-count of 6.736 which is greater than t-table 2.010 and a significance value of 0.000 which is smaller than 0.05. Furthermore, the simultaneous test (F test) shows that price (X1) and product quality (X2) together have a significant effect on consumer purchasing interest. The F-test results yielded an F-count of 24.591, which is greater than the F-table of 3.191, with a significance value of 0.000, indicating that both variables have a significant influence. The coefficient of determination indicates that price and product quality contribute 51.1% to consumer purchase intention, while the remaining 48.9% is influenced by other factors not examined in this study.